2022
DOI: 10.3389/fpubh.2022.931116
|View full text |Cite
|
Sign up to set email alerts
|

Developing healthy eating promotion mass media campaigns: A qualitative study

Abstract: BackgroundInvolving consumers in the development and assessment of mass media campaigns has been advocated, though research is still lacking. This study aimed to explore opinions and attitudes of citizens, health professionals, communication professionals, and digital influencers regarding the development and implementation of healthy eating promotion mass media campaigns.MethodsWe conducted five semi-structured focus groups, where participants were exposed to the first nationwide mass media campaign promoting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
3
0
3
Order By: Relevance
“…A study conducted using Facebook Live, a real-time online live streaming function, was able extend their reach to deliver nutrition education to lower income Americans (>16 years) [ 44 ]. A study conducted in Portuguese adults identified that short videos should be considered when developing mass media health promotion campaigns targeting healthy eating [ 45 ]. This was confirmed by a qualitative study conducted in young Australian women (18–35 years) that recommended that effective social media engagement should include engaging content such as videos [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted using Facebook Live, a real-time online live streaming function, was able extend their reach to deliver nutrition education to lower income Americans (>16 years) [ 44 ]. A study conducted in Portuguese adults identified that short videos should be considered when developing mass media health promotion campaigns targeting healthy eating [ 45 ]. This was confirmed by a qualitative study conducted in young Australian women (18–35 years) that recommended that effective social media engagement should include engaging content such as videos [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Os autores recomendaram a realização de mais estudos de modo a solidificar conclusões e a colocar recomendações mais precisas. Capitão et al (2022) desenvolveram um estudo qualitativo em Portugal, que pretendia conhecer a perspetiva dos profissionais de saúde e de comunicação, influenciadores digitais e cidadãos, acerca das campanhas de promoção de uma alimentação saudável. A investigação envolveu cinco grupos focais, que foram expostos a uma campanha nacional de promoção de uma alimentação saudável em Portugal.…”
Section: Revisão De Literaturaunclassified
“…Research indicates that consistent and engaging messaging can lead to improvements in employees' dietary habits. 21 Organisations should tailor their messaging tools to their specific workplace culture and employee population to maximize effectiveness.…”
Section: Messagingmentioning
confidence: 99%